2014
DOI: 10.1155/2014/608739
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonspecific, Glutamic Acid-Free, Media and High Glycerol or High Amylase as Inducing Parameters for ScreeningBacillusIsolates Having High Yield of Polyglutamic Acid

Abstract: Out of fifty-five Bacillus isolates obtained from ten different regional locations and sources, seven showed the ability to consistently produce specific extracellular polymeric substance (EPS) on rich as well as synthetic but nonspecific media which did not contain glutamic acid. The isolates were identified as either Bacillus licheniformis or Bacillus subtilis. The EPS from all isolates was resistant to alpha protease, proteinase K, and was thus of high molecular weight. Further it was detected after SDS-PAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Increasing the inoculum over 3% had a negative impact on PGA production. Our results were in the same line with Baxi, [37] investigation who assessed 5A). Similar results were also reported by [44,45,37] who found that the production of PGA dry weight incremented 2-fold when the media inoculated by young outgrowth vegetative cells at the age of 24 h when compared to another inoculum contained a mixture of outgrowth vegetative cells and spores.…”
Section: Physical State Of Inoculumsupporting
confidence: 93%
See 3 more Smart Citations
“…Increasing the inoculum over 3% had a negative impact on PGA production. Our results were in the same line with Baxi, [37] investigation who assessed 5A). Similar results were also reported by [44,45,37] who found that the production of PGA dry weight incremented 2-fold when the media inoculated by young outgrowth vegetative cells at the age of 24 h when compared to another inoculum contained a mixture of outgrowth vegetative cells and spores.…”
Section: Physical State Of Inoculumsupporting
confidence: 93%
“…Our results were in the same line with Baxi, [37] investigation who assessed 5A). Similar results were also reported by [44,45,37] who found that the production of PGA dry weight incremented 2-fold when the media inoculated by young outgrowth vegetative cells at the age of 24 h when compared to another inoculum contained a mixture of outgrowth vegetative cells and spores. In addition, PGA productivity, yield, and conversion coefficient were the most efficient at the same inoculum state (outgrowth vegetative cells) revealing (0.16 gl , 772.5%) for Bacillus and (0.14 gl -1 h -1 , 4.5 gg -1 , 738.6%) for strain, respectively (Fig.…”
Section: Physical State Of Inoculumsupporting
confidence: 93%
See 2 more Smart Citations
“…Microorganisms including bacteria, fungi, and algae can also participate in ZnO-NP biosynthesis, 47,48 as these microorganisms have a self-defense mechanism for heavy metal ion exposure. 49 The preparation process can be divided into microorganism cultivation, biochemical activities of microorganisms, intra-and extracellular transport of metal ions, intracellular nucleation, and finally NP formation. 35,49 Shamsuzzaman et al 50 used a Candida albicans suspension as a reducing and capping agent, and successfully prepared quasi-spherical ZnO-NPs with a diameter of ~15-20 nm.…”
Section: Green Fabrication Process Of Zno-npsmentioning
confidence: 99%